Conflitos conjugais: uma leitura a partir da psicologia analítica, tomando como base os tipos psicológicos - Gimael, Elizabeth do Rocio Dipp Azevedo (2008)
This research aimed to identify the conflicts experienced by couples that have been characterized with the Extrovert Feeling . Our study was based on the assumption that no marriage can exist without conflicts, and that conflicts occur not only between couples with the opposite typology but also between those with the same typology. Conflicts do not only occur only when casals have the opposite typological functions, but also when they have the same dominant functions. From our review of the literature we only identified one study that focused on the two issues. We identified several studies that considered conjugal conflicts, but very few that related these conflicts to psychological types. Considering that our study examined conjugal conflicts, the typology of couples and the possible relationship between the conflicts and their typology, an iniitial depth interview was considered to be an adequate procedure to approach this question, given that we did not intend to undertake a therapeutic process. We adopted a qualitative approach to this research, which consisted of two moments. During the first moment we identified the typology of the couples and during the second moment, three couples were selected and interviewed in order to investigate the conjugal conflicts they identified, and to relate these conflicts to their typology. The instrument used for this research was QUATI (Questionnaire to Evaluate Typology), which enabled us to select three couples from the twenty four couples who participated during the first stage of the research. Considering the difficult task of reconciling typology and conjugal conflicts, after evaluating the results and the data obtained and performing an intuitive, symbolic, conceptual analysis, we concluded that some conflicts reported by the couples could be related to their typology, but we understand that other studies need be undertaken in order to obtain more conclusive evidence